Indigenous knowledge and traditional conservation of fonio millet (Digitaria exilis, Digitaria iburua) in Togo. - ADOUKONOU-SAGBADJA, Hubert (My University, 2006)
Fonio millet (Digitaria exilis Stapf, Digitaria iburua Stapf) is known in Togo far several centuries and has played a strategic role in the household food security mainly in rural areas. Using Participatory Research Appraisal (PRA) tools and techniques, 55 villages randomly selected in the two production zones of Togo were surveyed to document the ethno-botanical and indigenous knowledge related to its production, diversity, use and conservation. For all of the ethnic groups involved in fonio production in Togo (Akposso and Ake ́bou in the south; Losso-Nawda, Lamba, Tamberma, Tchokossi and Gangan in the north), the crop has a high sociocultural value. The fonio genetic diversity being managed by the farmers seems important as 42 landraces were recorded. Two lines of origin that contributed to this current genetic diversity (local domestication or introduction from neighbouring countries) were reported by the farmers. Cooking qualities, growth cycle, colour and size of the grains are the main criteria used by farmers to describe varieties. According to farmers, fonio production and diversity are being regressing because of several constraints of which the most important are lack of adequate harvest, threshing and processing technologies and development of pests and diseases. The important ethnobotanical and indigenous data recorded will be useful in accessing the genetic diversity of the crop in Togo and in defining appropriate strategies for its conser- vation on farm.
Keywords: Digitaria; Ethnobotany; Fonio; Genetic resources management; On-farm conservation; Togo